The Influence of Labor, Female Population and Per Capita Income on Air Pollution in Indonesia - Wulandari, Ida Ayu Made Asdhi; Setyari, Ni Putu Wiwin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The Indonesian textile industry is one of the major economic pillars behind its contribution to the economy, the textile industry is also known as one of the largest contributors to environmental pollution. This study aims to determine the effect of the textile industry on environmental pollution in Indonesia. To show how the textile industry affects environmental pollution, three variables are used, namely labor, women, and per capita income. This study aims to analyze the effect of labor, women, and per capita income on environmental pollution in Indonesia both simultaneously and partially. The data in this study all use secondary data in the form of time series data for the period 1992-2022 obtained from the Indonesian Central Statistics Agency and the World Bank. The analysis technique used is multiple linear analysis using eviews. The results of the study show that the variables of labor, women and per capita income simultaneously affect environmental pollution in Indonesia. Partially, labor and per capita income do not affect environmental pollution in Indonesia, while women have a significant partial effect on environmental pollution in Indonesia. The results of this study have implications both theoretically and practically. Theoretically, these findings support the theory that women's participation in leadership or decision-making is often associated with more effective environmental policies.